MATHEMATICAL MODELING OF ELECTRIC MODES WITH ARF - Веприк, Юрий Николаевич; Лебедка, Сергей Николаевич (Eastern-European Journal of Enterprise Technologies, 2012)
The paper presents the results of studies of electromagnetic transients in power networks 6-10 kV with different modes of neutral and means of limiting the effectiveness of capacitive currents and surge in single-phase ground faults.